2004
DOI: 10.1097/01.jom.0000128161.17144.27
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Update of Workers Exposed to Acrylonitrile in The Netherlands

Abstract: To study the possible carcinogenic effects of acrylonitrile, we updated the follow up of a cohort of 2842 acrylonitrile workers. The comparison group consisted of 3961 workers from a nitrogen fixation plant. Industrial hygiene assessments quantified past exposure to acrylonitrile, 8-hour averages as well as peak exposure, the use of personal protective equipment, and exposure to other potential carcinogenic agents. Standardized mortality ratios were calculated to adjust for the effect of age distribution, leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 9 publications
0
28
0
Order By: Relevance
“…While some early studies reported small excesses of lung cancer mortality (Delzell and Monson, 1982;Monson and Fine, 1978;O'Berg, 1980;Swaen et al, 1992;Thiess et al, 1980), other studies (Collins et al, 1989;Mastrangelo et al, 1993), as well as follow-up studies of the initial positive cohorts (O'Berg et al, 1985;Swaen et al, 1998Swaen et al, , 2004Wood et al, 1998), have reported no such excess or have reported small deWcits. Table 1 Exposure-response data for lung and brain cancer mortality from three cohorts of workers exposed to AN a External exposure and SMR values for each decile and quartile from Youk and Marsh (personal communication, 2004) except where otherwise noted.…”
Section: An Data From Epidemiology Studiesmentioning
confidence: 93%
See 2 more Smart Citations
“…While some early studies reported small excesses of lung cancer mortality (Delzell and Monson, 1982;Monson and Fine, 1978;O'Berg, 1980;Swaen et al, 1992;Thiess et al, 1980), other studies (Collins et al, 1989;Mastrangelo et al, 1993), as well as follow-up studies of the initial positive cohorts (O'Berg et al, 1985;Swaen et al, 1998Swaen et al, , 2004Wood et al, 1998), have reported no such excess or have reported small deWcits. Table 1 Exposure-response data for lung and brain cancer mortality from three cohorts of workers exposed to AN a External exposure and SMR values for each decile and quartile from Youk and Marsh (personal communication, 2004) except where otherwise noted.…”
Section: An Data From Epidemiology Studiesmentioning
confidence: 93%
“…A large amount of information has been collected over the past 22 years, much of which can be used to speciWcally address data gaps identiWed by USEPA in their 1983 assessment, including the following (numbers in parentheses correspond to numbered data gaps listed in the introduction): (1) several large well-designed, epidemiology studies have been conducted including those with extensive exposure information (Blair et al, 1998;Swaen et al, 1998Swaen et al, , 2004Wood et al, 1998); (2) two follow-up studies have been conducted for the O'Berg (1980) cohort (O'Berg et al, 1985;Wood et al, 1998); (3) a three-generation reproductive toxicity study in rats has been published for AN (Friedman and Beliles et al, 2002); (4) additional cancer bioassays have been conducted for AN using mice following oral exposure (NTP, 2001) and rats following oral and inhalation exposure (Bigner et al, 1986;Ghanayem et al, 2002;Maltoni et al, 1988); (5) an in vitro cell transformation study has been conducted for AN in Syrian hamster embryo cells (Zhang et al, 2000); (6) a number of mechanistic studies have been conducted for AN that demonstrate a role for oxidative stress in the formation of rat brain tumors (Jiang et al, 1998;Kamendulis et al, 1999a;Murata et al, 2001;Whysner et al, 1998a;Zhang et al, 2002); (7) a large amount of pharmacokinetic data has been collected and compiled into physiologically based pharmacokinetic (PBPK) models for AN in rats (Gargas et al, 1995;Kedderis and Fennell, 1996) and humans (Sweeney et al, 2003); (8) a mutagenicity study has been conducted for AN in human lymphoblasts (Recio and Skopek, 1988); and (9) dominant lethal studies have been conducted for AN (Working et al, 1987;Butterworth et al, 1992).…”
Section: Identiwcation Of Critical Data Setsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Literature data on individual acrylic components are extensive and very often quite controversial (Dearfield et al 1988;Butterworth et al 1992;Bergmark 1997;Bjorge et al 1996), irrespective of whether the data were obtained from animal experiments or from exposed subjects (Benn and Osborne 1998;Blair et al 1998;Stewart et al1998;Swaen et al 1998;Wood et al 1998). Despite the fact that a large number of these substances are supposed to exhibit carcinogenic properties, the results of several recently published studies on the occurrence of malignancies in individuals who were occupationally exposed to acrylonitrile showed, on the contrary, that the occurrence of malignancies was lower than expected.…”
Section: Introductionmentioning
confidence: 98%
“…Substantial evidence that lung cancer mortality is not associated with acrylonitrile exposure has been obtained from four large acrylonitrile worker cohort studies: NCI (Blair et al [2]), DuPont (Symons et al [3]), Dutch (Swaen et al [4]), and United Kingdom (Benn and Osborne [5]), as well as from independent studies of subcohorts of workers from two of the NCI study sites in Fortier, LA/Santa Rosa, FL (Collins et al [6]) and Lima, OH (Marsh and Zimmerman [7]). Nevertheless, in 2014, Kopylev [1] speculated that a significant positive association may have been missed in the Blair et al [2] analysis because the NCI investigators did not employ the "correct" metric for acrylonitrile exposure.…”
Section: Introductionmentioning
confidence: 99%